Resultados e perspectivas do Programa Professor Visitante Sênior (PVS), como política pública, no fortalecimento da Pós-Graduação Stricto Sensu: um estudo de caso na UNILA - Borges, Carolina Costa (2018)
This research was developed under the Stricto Sensu Post Graduation Program in Education at Universidade Católica de Brasília - UCB, in the research line “Politics, Management and Economics of Education”, and the objective of this is to investigate a public promotion policy conceived by Fundação Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – CAPES, linked to Ministério da Educação – MEC and implemented by Universidade Federal da Integração Latino Americana (UNILA), with the aim of forming qualified and experienced groups to act in research, teaching and extension, aiming to contribute with the consolidation of the innovative project of this university. The method used is the Case Study one, proposed by Robert Yin, with a qualitative and exploratory approach. The techniques used for the analysis of the data were a bibliographical and documentary survey, with the purpose of verifying how the program developed. Besides that, the documentary survey was complemented by semi-structured interviews with teachers who participated in the program at the UNILA. The collected material data were analyzed using Bardin's Content Analysis theory, seeking to understand the perception of the visiting professor as a collaborator in UNILA and its performance in meeting the goals established in the program. The results demonstrated the achievement of established goals, as well as the positive impact on the academic-scientific improvement of the university.